High-activity composite auxiliary cementing material based on carbonated steel slag-carbide slag as well as preparation method and application of high-activity composite auxiliary cementing material
By using highly active composite auxiliary gelling materials composed of carbonated steel slag-calcium slag composite fine powder and high-titanium slag, metakaolin, phosphogypsum, etc., the problems of low carbon sequestration rate and insufficient activity in the existing high-calcium-containing solid waste carbon sequestration technology are solved, and high-efficiency carbon sequestration and material activity are improved, with good environmental benefits and application prospects.
Patent Information
- Application Number
- CN202411848780.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The existing carbon sequestration technology of high calcium-containing solid waste has problems such as low carbon sequestration rate, complex processes, and difficult application of products. The steel slag activity is low and the calcium carbide slag contains polluted components, which affects the environment.
A highly active composite auxiliary gelling material composed of carbonated steel slag-calcium slag composite fine powder and high-titanium slag, metakaolin, phosphogypsum, etc. is used to improve carbon sequestration rate and activity and reduce pollution through carbonization reaction and alkali excitation.
It significantly improves carbon sequestration efficiency and activity, improves the stability and application range of materials, slows down the activity of steel slag due to carbonization, and has good environmental benefits.
Smart Images

Figure BDA0005190002710000091 
Figure BDA0005190002710000101 
Figure BDA0005190002710000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag and a preparation method and application thereof. Background Art
[0002] Cement is an important resource and a basic product that affects the development of the national economy. Since its introduction, it has been one of the most widely used engineering materials because of its convenient raw material acquisition, high construction flexibility and low price. It is still an irreplaceable basic building material. As a core building material, cement has huge carbon emissions and is one of the main sources of carbon emissions in my country. Its carbon emissions in 2020 were about 1.37 billion tons, accounting for about 13% of the country's total carbon emissions; direct carbon emissions were about 1.23 billion tons, accounting for 84.3% of the total carbon emissions in the building materials industry. On the other hand, with the advancement of the new national standard GB 175-2023 "General Portland Cement", it has promoted the improvement of material quality and green and low-carbon transformation, and promoted the standardization and sustainable development of the industry, but the price of cement has also risen, so finding a greener and lower-carbon cementitious material has become an urgent problem to be solved.
[0003] Applying industrial waste residue as a mineral admixture in concrete can significantly save resources, reduce energy consumption, and reduce environmental load. On the one hand, it can reduce the amount of cement used and carbon emissions. On the other hand, it can reduce the cost of concrete, which is more conducive to reducing the pressure of industrial waste residue on the environment and reducing the air pollution caused by the production of cement concrete industry. It has good economic and social benefits and is an inevitable way to achieve low-carbon concrete. In recent years, the use of industrial solid waste rich in calcium and magnesium to mineralize and absorb CO 2 Methods have gradually emerged. Taking steel slag, carbide slag and phosphogypsum, which are bulk industrial solid wastes with high calcium content, as examples, the main components are CaO, Ca(OH) 2 and CaSO 4 These calcium-containing minerals can mineralize and absorb CO under certain conditions. 2 , with a huge fixed CO 2 potential.
[0004] However, the carbon fixation of high-calcium solid waste often has problems such as low carbon fixation rate, complex process, and difficult application of generated products. Solid waste itself also has certain problems, such as low activity and poor stability of steel slag; carbide slag contains some sulfides and phosphides; there are some organic matter, fluoride, heavy metal ions, etc. in phosphogypsum, so the accumulation of the three will have a great impact on the environment. Therefore, in order to meet the growing demand for infrastructure construction, the development of green and low-carbon industrial solid waste mineral admixtures is an inevitable trend in the future. Solving the problem of low utilization rate of existing solid waste is conducive to promoting the green, low-carbon and sustainable development of cement concrete engineering, and has important strategic opportunities and broad development prospects. Summary of the invention
[0005] The technical problem to be solved by the present invention is to address the deficiencies in the prior art and to provide a high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag and a preparation method and application thereof. The high-activity composite auxiliary cementitious material is composed of carbonated steel slag-carbide slag composite powder and other industrial solid wastes, has a high carbon fixation rate and has high activity and stability, and has broad application prospects in cement mortar or concrete.
[0006] In order to solve the technical problem proposed by the present invention, the present invention provides a high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag, comprising the following raw materials in parts by weight: 40 to 55 parts of carbonated steel slag-carbide slag composite micropowder, 30 to 40 parts of high-titanium slag, 20 to 25 parts of metakaolin, and 3 to 5 parts of phosphogypsum.
[0007] In the above scheme, the carbonated steel slag-carbide slag composite micropowder is obtained by carbon fixation reaction of steel slag and carbide slag in a solution consisting of a carbonization enhancer, an additive and water.
[0008] In the above scheme, the method for preparing the carbonated steel slag-carbide slag composite micropowder comprises the following steps:
[0009] 1) Grinding steel slag and a grinding aid in a ball mill to obtain steel slag powder;
[0010] 2) mixing steel slag powder and carbide slag evenly to obtain steel slag-carbide slag composite powder;
[0011] 3) Mix the carbonization enhancer and water evenly, then add steel slag-carbide slag composite powder and additives in sequence, stir evenly, place in a carbonization reactor, and introduce CO 2 Carry out carbon fixation reaction;
[0012] 4) After the carbon fixation reaction is completed, solid-liquid separation is performed, ethanol is added to the solid material to terminate hydration, and the solid material is dried to obtain carbonated steel slag-carbide slag composite micropowder.
[0013] Furthermore, in the preparation method of the carbonated steel slag-carbide slag composite micropowder, the mass proportions of the raw materials used are: 20-35 parts of steel slag, 15-20 parts of carbide slag, 0.05-0.1 parts of grinding aid, 0.1-0.5 parts of carbonization enhancer, 0.05-0.1 parts of additives, and 280-550 parts of water.
[0014] Furthermore, the mass of the water is 8 to 10 times the sum of the mass of the steel slag and the carbide slag.
[0015] Furthermore, the steel slag is converter steel slag, which is a high-temperature solid solution waste slag formed by a mixture of slag-making materials, smelting materials, furnace lining and various metal impurities during the steelmaking process, and is subjected to aging treatment at room temperature or by water sprinkling cooling, and then crushed and magnetically separated to remove iron to obtain steel slag particles with a particle size of 1 to 2 cm.
[0016] Furthermore, the grinding aid is composed of sodium tripolyphosphate and triisopropanolamine, and the mass ratio of sodium tripolyphosphate to triisopropanolamine is 1:(2.5-3).
[0017] Furthermore, the grinding time is 1 to 1.5 hours, and the specific surface area of the steel slag powder is ≥450m 2 / kg.
[0018] Furthermore, the carbide slag is carbide slag that has been dried and stored in a vacuum dryer to remove a large amount of free water and some harmful gases such as hydrogen sulfide, phosphine, and acetylene residual gas and prevent them from reacting with CO in the air. 2 Natural weathering reaction occurs, and its moisture content is less than 1%, Ca(OH) 2 The content is not less than 75%, and the specific surface area is 520~570m 2 / kg.
[0019] Furthermore, the carbonization enhancer is composed of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate, and the mass ratio of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate is (1.4-2):(3.8-4.4):1.5.
[0020] Furthermore, the sodium tripolyphosphate is an analytically pure chemical reagent with a content of ≥98%.
[0021] Furthermore, the sodium citrate is an analytically pure chemical reagent with a content of ≥99%.
[0022] Furthermore, the MSG waste slurry is wastewater generated by producing MSG through fermentation using economic crops with high starch content such as corn and rice, and is rich in amino and hydroxyl groups, with an L-glutamic acid content of 1.5-2%, a crude protein content of 70-80%, and a pH value of 3-4.
[0023] Furthermore, the additive is a mixture of polyvinyl alcohol and hydrogen peroxide, the concentration of hydrogen peroxide is 1-1.2 mol / L, and the mass ratio of polyvinyl alcohol to hydrogen peroxide is (1.2-1.7):1.
[0024] Furthermore, the reaction temperature of the carbon fixation reaction is 50-60°C, the reaction time is 60-90 min, and CO 2 The pressure is 0.3~0.5MPa.
[0025] Furthermore, the ethanol needs to submerge the solid material and keep soaking for 0.8 to 1 day.
[0026] Furthermore, the drying temperature is 60-65° C. and the drying time is 6-7 hours.
[0027] In the above scheme, the high-titanium slag is water-quenched high-titanium slag, which is a black-gray powder obtained by crushing and grinding the molten slag produced by smelting pig iron with vanadium-titanium magnetite, and its main components are CaO, SiO 2 、TiO 2 、Al 2 O 3 , TiO 2 The content is 10% to 15%, and the specific surface area is 500 to 550m 2 / kg, density is 2.6~2.9g / cm 3 .
[0028] In the above scheme, the metakaolin is a highly active amorphous white powder obtained by calcining kaolin at 750-800°C. 2 and Al 2 O 3 The total content is ≥94.5%, the particle size is ≤20μm, the 2h ignition loss is 0.26~0.28, and the 28d activity index is 106~108%.
[0029] In the above scheme, the phosphogypsum is hemihydrate phosphogypsum (CaSO 4 1 / 2H 2 O), which is a byproduct of the semi-aqueous wet phosphoric acid process for preparing phosphate fertilizer, is dried at 60-65°C to constant weight, and then ground by a ball mill to obtain a fine powder with a pH of 5.6-6.0 and a density of 2.2-2.4 g / cm 3 , with a specific surface area of 450-520m 2 / kg.
[0030] The present invention also provides a method for preparing a high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag, comprising the following steps:
[0031] The carbonated steel slag-carbide slag composite powder, high-titanium slag, metakaolin and phosphogypsum are uniformly mixed to obtain a high-activity composite auxiliary cementitious material.
[0032] The present invention also provides an application of a high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag, and the application method is: using the high-activity composite auxiliary cementitious material to replace part of cement to prepare mortar or concrete.
[0033] In the above solution, the mass replacement rate of the high-activity composite auxiliary cementitious material for cement is not higher than 50%.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The steel slag and carbide slag of the present invention are both high-calcium solid wastes. On the one hand, under certain conditions, both can mineralize and absorb CO 2 The synergistic effect of the two can significantly improve the carbon fixation efficiency, thereby achieving the goal of efficient carbon fixation; on the other hand, the activity of steel slag is relatively low. After carbonization, the RO phase and the free phase (f-CaO and f-MgO) are decomposed, and the active mineral C 3 S and C 2 S is also partially reacted, resulting in further reduction in activity. The majority of carbide slag is Ca(OH) 2 The activity of slag is still very high after carbonization reaction. The two complement each other to slow down the decrease of activity of slag caused by carbonization, and significantly improve its activity while achieving high carbonization efficiency. Finally, solid waste is used to adsorb CO 2 , achieving the goal of "waste treatment with waste" and has good environmental benefits.
[0036] (2) The steel slag and carbide slag of the present invention both adopt an indirect method for carbon fixation, using a leaching solution to react with the former two, and after calcium, magnesium, etc. are leached, they are reacted with CO 2 Carbonate precipitation is formed by the reaction. The factors affecting carbonization are mainly concentrated in two aspects: ① leaching of calcium and magnesium in the early particles into the liquid phase; ② subsequent CO 2 The high pH value in the early stage of carbonization hinders the leaching of calcium, while the low pH value in the late stage of carbonization hinders the leaching of CO 2 The dissolution of slag and carbide slag seriously limits the carbonization efficiency of slag and carbide slag. The present invention uses sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate as carbonization enhancers, wherein sodium tripolyphosphate and sodium citrate are chelating agents and pH regulators, and have the ability to chelate calcium and magnesium ions and adjust pH values, and can adjust the pH value of the entire carbonization process, reduce the pH value in the early stage to increase the leaching of calcium and magnesium ions in slag and carbide slag, and increase the pH value in the later stage to increase CO 2 dissolution, improving the leaching of calcium and magnesium ions in steel slag while promoting CO 2The absorption of carbon can significantly improve the carbon fixation rate of steel slag and carbide slag; the monosodium glutamate waste slurry is acidic and rich in L-glutamic acid and crude protein. The acidic condition is convenient for the leaching of calcium and magnesium ions. L-glutamic acid can significantly improve the leaching rate of calcium and magnesium ions. The hydroxyl and carboxyl groups can be effectively adsorbed on the surface of steel slag and carbide slag, which enhances the particle dispersion. The amino groups in crude protein can absorb CO 2 , promoting CO 2 Combining the pH adjustment and chelating properties of sodium tripolyphosphate and sodium citrate with the calcium and magnesium ion leaching, dispersion and CO 2 The absorption performance can significantly improve the carbon fixation efficiency of steel slag and carbide slag.
[0037] (3) In addition to the chelating ability and the ability to adjust the pH value in the carbon fixation reaction of steel slag and carbide slag, the sodium tripolyphosphate and sodium citrate of the present invention also play other roles: sodium tripolyphosphate is used as a grinding aid for steel slag and is combined with triisopropanolamine to improve the grinding efficiency of steel slag and reduce working energy consumption; sodium citrate has a retarding property, thereby effectively reducing the hydration reaction rate of steel slag and carbide slag in the wet carbonization process, reducing the activity reduction of the two after the carbonization reaction, and effectively improving the activity of solid waste admixtures.
[0038] (4) During the carbonization reaction of the present invention, calcium carbonate and magnesium carbonate are generated and closely aggregated on the surface of steel slag powder and carbide slag powder, blocking CO 2 The dissolution efficiency of polyvinyl alcohol and hydrogen peroxide can be improved. The additive polyvinyl alcohol and hydrogen peroxide can reduce the "partition effect" caused by the close aggregation of calcium carbonate and magnesium carbonate. When the polyvinyl alcohol solution is mixed with steel slag powder and calcium carbide slag powder, a thin layer of PVA is formed on the particles. During the carbonation process, PVA foams under pressure to produce bubbles and a film containing carbon dioxide, thereby increasing gas retention and promoting more thorough carbonization; hydrogen peroxide can disintegrate the silicon-rich product layer generated by the leaching reaction and depolymerize it into particles with small molecular weight, thereby improving CO 2 The efficiency of carbonization reaction is improved, which reduces the energy barrier required for the subsequent carbonization reaction and significantly enhances the carbonization effect. The two complement each other and can significantly improve the carbonization reaction process and improve the carbon fixation efficiency.
[0039] (5) The present invention uses carbonized steel slag-carbide slag composite powder and high-titanium slag, metakaolin and phosphogypsum to form a composite auxiliary gelling material. The carbonized steel slag-carbide slag composite powder and high-titanium slag promote the formation of carbon aluminate and the volcanic ash reaction of amorphous silicon-aluminum phase under the alkali excitation of metakaolin and phosphogypsum, thereby producing more C-(A)-SH gel, thereby dramatically improving its potential activity; the selected several different industrial solid wastes contain aluminate (amorphous C 12 A 7 ), silicate (β-C 2S), carbonates, sulfates and active SiO 2 The mineral phase characteristics such as alkali excitation can achieve the effect. By adjusting the proportion of components, the performance of the auxiliary cementitious material of the present invention can be adjusted and controlled to meet or match the requirements of different cement concrete materials, thereby greatly improving its adaptability and application range. The addition of metakaolin can significantly improve the appearance of cement hydration products, forming a network structure that is more compact and more effective in absorbing sulfides, phosphides, fluorides, heavy metal ions, etc. in carbide slag and phosphogypsum, solidifying them inside the building structure, and reducing their pollution to the environment. On the one hand, it overcomes the shortcomings of steel slag and high-titanium slag as auxiliary cementitious materials, which lead to slow strength development and low early strength of cementitious materials due to their low activity. On the other hand, it also improves the low application rate of construction solid wastes such as carbide slag and phosphogypsum due to their own pollution properties, and achieves high-efficiency application of solid wastes. Specific implementation methods
[0041] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0042] In the following embodiments, the steel slag used is converter steel slag, which is a high-temperature solid solution waste slag formed by mixing slag-making materials, smelting materials, furnace lining and various metal impurities in the steelmaking process, and is subjected to room temperature or water cooling and aging treatment, and then crushed and magnetically separated to remove iron to obtain steel slag particles with a particle size of 1 to 2 cm;
[0043] The carbide slag used was dried at 105°C and then stored in a vacuum dryer for 48 hours. The moisture content was less than 1%, and the Ca(OH) 2 The content is 76% and the specific surface area is 550m 2 / kg;
[0044] The sodium tripolyphosphate used is an analytically pure chemical reagent with a content of ≥98%; the sodium citrate is an analytically pure chemical reagent with a content of ≥99%.
[0045] The monosodium glutamate waste slurry used is the wastewater produced by fermentation of monosodium glutamate from economic crops with high starch content such as corn and rice. It is rich in amino and hydroxyl groups, with an L-glutamic acid content of 1.8%, a crude protein content of 75%, and a pH value of 3.5.
[0046] The high-titanium slag used is water-quenched high-titanium slag, which is a black-gray powder obtained by crushing and grinding the molten slag produced by smelting pig iron with vanadium-titanium magnetite, and its main components are CaO, SiO 2 、TiO 2 、Al 2 O 3 , TiO 2The content is 13%, and the specific surface area is 540m 2 / kg, density is 2.6g / cm 3 ;
[0047] The metakaolin used was a highly active amorphous white powder obtained by calcining kaolin at 750°C. 2 and Al 2 O 3 The total content is 94.5%, the particle size is ≤20μm, the 2h ignition loss is 0.26, and the 28d activity index is 106%;
[0048] The phosphogypsum used is hemihydrate phosphogypsum (CaSO 4 1 / 2H 2 O), which is a byproduct of the semi-aqueous wet phosphoric acid process for preparing phosphate fertilizer, is dried at 60°C to constant weight and then ground by a ball mill to obtain a fine powder with a pH value of 5.6 and a density of 2.4 g / cm 3 , with a specific surface area of 505m 2 / kg.
[0049] Example 1
[0050] A high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag comprises the following raw materials in parts by mass: 42 parts of carbonated steel slag-carbide slag composite micropowder, 32 parts of high-titanium slag, 21 parts of metakaolin, and 3.6 parts of phosphogypsum. The above raw materials are mixed and stirred evenly to obtain the high-activity composite auxiliary cementitious material.
[0051] The method for preparing the carbonated steel slag-carbide slag composite powder comprises the following steps:
[0052] 1) 21 parts of steel slag and 0.05 parts of grinding aid (composed of sodium tripolyphosphate and triisopropanolamine in a mass ratio of 1:2.5) were placed in a ball mill and ground for 1 hour to obtain a specific surface area of 458m 2 / kg of steel slag powder;
[0053] 2) mixing steel slag powder and 16 parts of carbide slag evenly to obtain steel slag-carbide slag composite powder;
[0054] 3) 0.16 parts of carbonization enhancer (composed of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate in a ratio of 1.5:3.8:1.5) was mixed evenly with 303 parts of deionized water, and then steel slag-carbide slag composite powder and 0.05 parts of additive (composed of polyvinyl alcohol and 1 mol / L hydrogen peroxide in a mass ratio of 1.2:1) were added in sequence. After mixing evenly, the mixture was placed in a carbonization reactor and CO was introduced. 2 Carbon fixation reaction, CO 2 The pressure was 0.31 MPa, the reaction temperature was 50°C, and the reaction time was 65 min;
[0055] 4) After the carbon fixation reaction is completed, the solid-liquid separation is carried out, the leached liquid is collected and reused, and ethanol is added to the solid material to terminate the hydration. The ethanol needs to submerge the solid material and keep soaking for 0.8 days. The solid-liquid separation is carried out again, and the solid material is dried in an oven at 60°C for 6 hours to obtain carbonated steel slag-carbide slag composite micropowder.
[0056] Example 2
[0057] A high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag comprises the following raw materials in parts by mass: 45 parts of carbonated steel slag-carbide slag composite micropowder, 35 parts of high-titanium slag, 20 parts of metakaolin, and 4 parts of phosphogypsum. The above raw materials are mixed and stirred evenly to obtain the high-activity composite auxiliary cementitious material.
[0058] The method for preparing the carbonated steel slag-carbide slag composite powder comprises the following steps:
[0059] 1) 25 parts of steel slag and 0.07 parts of grinding aid (composed of sodium tripolyphosphate and triisopropanolamine in a mass ratio of 1:2.7) were placed in a ball mill and ground for 1 hour to obtain a specific surface area of 503m 2 / kg of steel slag powder;
[0060] 2) mixing steel slag powder and 16 parts of carbide slag evenly to obtain steel slag-carbide slag composite powder;
[0061] 3) 0.21 parts of carbonization enhancer (composed of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate in a ratio of 1.7:4:1.5) was mixed evenly with 365 parts of deionized water, and then steel slag-carbide slag composite powder and 0.06 parts of additive (composed of polyvinyl alcohol and 1 mol / L hydrogen peroxide in a mass ratio of 1.4:1) were added in sequence. After mixing evenly, the mixture was placed in a carbonization reactor and CO was introduced. 2 Carbon fixation reaction, CO 2 The pressure was 0.33 MPa, the reaction temperature was 54 °C, and the reaction time was 72 min;
[0062] 4) After the carbon fixation reaction is completed, solid-liquid separation is carried out, and the leached liquid is collected and reused. Ethanol is added to the solid material to terminate hydration. The ethanol needs to submerge the solid material and keep soaking for 0.9 days. The solid-liquid separation is carried out again, and the solid material is dried in an oven at 65°C for 6.3 hours to obtain carbonated steel slag-carbide slag composite micropowder.
[0063] Example 3
[0064] A high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag comprises the following raw materials in parts by mass: 49 parts of carbonated steel slag-carbide slag composite micropowder, 38 parts of high-titanium slag, 22 parts of metakaolin, and 3.6 parts of phosphogypsum. The above raw materials are mixed and stirred evenly to obtain the high-activity composite auxiliary cementitious material.
[0065] The method for preparing the carbonated steel slag-carbide slag composite powder comprises the following steps:
[0066] 1) 32 parts of steel slag and 0.07 parts of grinding aid (composed of sodium tripolyphosphate and triisopropanolamine in a mass ratio of 1:2.8) were placed in a ball mill and ground for 1 hour to obtain a specific surface area of 520m 2 / kg of steel slag powder;
[0067] 2) mixing steel slag powder and 20 parts of carbide slag evenly to obtain steel slag-carbide slag composite powder;
[0068] 3) 0.35 parts of carbonization enhancer (composed of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate in a ratio of 1.8:4.2:1.5) was mixed evenly with 494 parts of deionized water, and then steel slag-carbide slag composite powder and 0.07 parts of additive (composed of polyvinyl alcohol and 1.1 mol / L hydrogen peroxide in a mass ratio of 1.5:1) were added in sequence. After mixing evenly, the mixture was placed in a carbonization reactor and CO was introduced. 2 Carbon fixation reaction, CO 2 The pressure was 0.44 MPa, the reaction temperature was 55°C, and the reaction time was 85 min;
[0069] 4) After the carbon fixation reaction is completed, the solid-liquid separation is carried out, the leached liquid is collected and reused, and ethanol is added to the solid material to terminate the hydration. The ethanol needs to submerge the solid material and keep soaking for 1 day. The solid-liquid separation is carried out again, and the solid material is dried in an oven at 60°C for 6.5 hours to obtain carbonated steel slag-carbide slag composite micropowder.
[0070] Example 4
[0071] A high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag comprises the following raw materials in parts by mass: 52 parts of carbonated steel slag-carbide slag composite micropowder, 36 parts of high-titanium slag, 25 parts of metakaolin, and 4.5 parts of phosphogypsum. The above raw materials are mixed and stirred evenly to obtain the high-activity composite auxiliary cementitious material.
[0072] The method for preparing the carbonated steel slag-carbide slag composite powder comprises the following steps:
[0073] 1) 34 parts of steel slag and 0.08 parts of grinding aid (composed of sodium tripolyphosphate and triisopropanolamine in a mass ratio of 1:3) were placed in a ball mill and ground for 1 hour to obtain a specific surface area of 550m 2 / kg of steel slag powder;
[0074] 2) mixing steel slag powder and 19 parts of carbide slag evenly to obtain steel slag-carbide slag composite powder;
[0075] 3) 0.44 parts of carbonization enhancer (composed of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate in a ratio of 2:4.4:1.5) was mixed evenly with 530 parts of deionized water, and then steel slag-carbide slag composite powder and 0.08 parts of additive (composed of polyvinyl alcohol and 1.2 mol / L hydrogen peroxide in a mass ratio of 1.6:1) were added in sequence. After mixing evenly, the mixture was placed in a carbonization reactor and CO was introduced. 2 Carbon fixation reaction, CO 2 The pressure is 0.47MPa, the reaction temperature is 60℃, and the reaction time is 90min;
[0076] 4) After the carbon fixation reaction is completed, the solid-liquid separation is carried out, the leached liquid is collected and reused, and ethanol is added to the solid material to terminate the hydration. The ethanol needs to submerge the solid material and keep soaking for 1 day. The solid-liquid separation is carried out again, and the solid material is dried in an oven at 65°C for 7 hours to obtain carbonated steel slag-carbide slag composite micropowder.
[0077] Comparative Example 1
[0078] The difference between Comparative Example 1 and Example 4 is that: in the preparation process of carbonated steel slag-carbide slag composite micropowder, the grinding aid is composed of sodium tripolyphosphate and triisopropanolamine in a mass ratio of 1:1, and step 1) obtains a specific surface area of 362m 2 / kg of steel slag powder.
[0079] Comparative Example 2
[0080] The difference between Comparative Example 2 and Example 4 is that during the preparation of the carbonated steel slag-carbide slag composite micropowder, 530 parts of deionized water are reduced to 315 parts of deionized water.
[0081] Comparative Example 3
[0082] The only difference between Comparative Example 3 and Example 4 is that no carbonization enhancer is used in the preparation process of the carbonated steel slag-carbide slag composite micropowder.
[0083] Comparative Example 4
[0084] The difference between Comparative Example 4 and Example 4 is that no additive is used in the preparation process of the carbonated steel slag-carbide slag composite micropowder.
[0085] Comparative Example 5
[0086] The difference between Comparative Example 5 and Example 4 is that during the preparation of the carbonated steel slag-carbide slag composite micropowder, the conditions for the carbon fixation reaction are adjusted to: CO2 The pressure is 0.6MPa, the reaction temperature is 80℃, and the reaction time is 120min.
[0087] Comparative Example 6
[0088] The only difference between Comparative Example 6 and Example 4 is that 52 parts of carbonated steel slag-carbide slag composite powder in the high-activity composite auxiliary cementitious material are replaced with 52 parts of carbonated steel slag powder.
[0089] The preparation method of carbonated steel slag micropowder is different from the preparation method of carbonated steel slag-carbide slag composite micropowder in that: step 2) is removed, carbide slag is not used, and the 34 parts of steel slag in step 1) are increased to 53 parts of steel slag to finally obtain carbonated steel slag micropowder.
[0090] Comparative Example 7
[0091] The only difference between Comparative Example 7 and Example 4 is that the carbonated steel slag-carbide slag composite micropowder in the high-activity composite auxiliary cementitious material is replaced by the steel slag-carbide slag composite micropowder obtained in step 2).
[0092] Application Examples
[0093] The high-activity composite auxiliary cementitious materials prepared in each embodiment and each comparative example are respectively used, and the application method is: the high-activity composite auxiliary cementitious materials are used to replace part of cement to prepare mortar or concrete.
[0094] Performance Testing
[0095] (1) Carbon fixation rate: The carbonized composite powder samples prepared in Examples 1 to 4 and Comparative Examples 1 to 6 were tested by measuring the mass change of the samples before and after carbonization. The carbon fixation rate was calculated as shown in Formula (1):
[0096]
[0097] In formula (1), ω CO2 is the carbon fixation rate, m 1 is the dry mass of the composite powder after carbonization, m 0 It is the dry mass of composite powder before carbonization.
[0098] (2) Activity index and volume stability: The high-activity composite auxiliary cementitious materials prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were used to replace 30% (mass replacement rate) of P·O42.5 cement to prepare mortar specimens. At the same time, pure cement was used for the test, numbered 0. The mortar activity index and volume stability were tested with reference to the methods in standards GB / T1596-2017 "Fly ash used in cement and concrete" and GB / T1346-2011 "Test methods for water consumption, setting time and stability of cement at standard consistency". The volume stability test method used the Leclerc clamp method.
[0099] (3) Porosity: The high-activity composite auxiliary cementitious materials prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were used to replace 50% (mass replacement rate) of P·O42.5 cement to prepare slurry specimens. Pure cement was used for the test and numbered as 0. After 28 days of age, the intermediate fragments were crushed and soaked in alcohol for 24 hours, and dried in an oven at 60°C for 2-3 hours. The porosity of the samples was then tested using a mercury intrusion tester.
[0100] (4) Chloride ion penetration resistance of concrete: The high-activity composite auxiliary cementitious materials prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were used to replace 30% (mass replacement rate) of P·O42.5 cement to prepare concrete specimens. At the same time, pure cement was used to carry out the test, numbered No. 0. The formula of No. 0 concrete was: cement 430 kg / m 3 、Medium sand 790kg / m 3 、Crushed stone 1040kg / m 3 , admixture 7kg / m 3 , water 150kg / m 3 The test was carried out in accordance with the electric flux method of the national standard GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The concrete specimen was a cylindrical specimen with a diameter of 100±1mm and a height of 50±2mm.
[0101] The performance test results are shown in Table 1.
[0102] Table 1 is a comparison table of experimental data of comparative examples and embodiments
[0103]
[0104]
[0105] From the data of Examples 1 to 4, No. 0 and Comparative Examples 1 to 6 in Table 1, it can be seen that the composite auxiliary cementitious material is prepared by carbonization modification of steel slag and carbide slag. As the carbon fixation rate increases, the expansion value decreases, the activity index increases, the porosity of the composite auxiliary cementitious material-cement slurry decreases, and the electric flux decreases. It can be concluded that carbonization modification can significantly improve the stability, strength, compactness and durability of the cementitious system.
[0106] By comparing Example 4 with Example 0, the results show that after the high-activity composite auxiliary cementitious material of carbonated steel slag-carbide slag replaces cement, the various properties of cement mortar concrete are improved, the activity index exceeds 100%, the porosity is reduced, and the concrete's resistance to chloride ion penetration is significantly enhanced. This indicates that when the high-activity composite auxiliary cementitious material of carbonated steel slag-carbide slag is used, it reacts synergistically with cement, the hydration reaction rate is increased, the hydration products fill the pores, and the concrete structure is dense, so various performance indicators are improved.
[0107] Comparing Example 4 with Comparative Examples 1 to 7, the results show that when the specific surface area of the steel slag powder is low, the carbon fixation rate decreases, the expansion value increases, the activity index significantly decreases, the porosity significantly increases, and the electric flux increases; when the ratio of deionized water / steel slag powder to carbide slag powder is reduced, the carbon fixation rate decreases, the expansion value increases, the activity index decreases, the porosity increases, and the electric flux increases; when there is no carbonization enhancer, the carbon fixation rate significantly decreases, the expansion value increases, the activity index decreases to a large extent, and the porosity significantly increases; when there is no additive, the carbon fixation rate significantly decreases, the expansion value increases, the activity index decreases to a large extent, and the porosity significantly increases. When the carbonization reaction temperature, reaction time and pressure are increased, the performance parameters remain basically unchanged, but the energy consumption is large, which is not worth the cost. After replacing all the carbide slag with steel slag, the carbon fixation rate is significantly reduced, the expansion value is increased, the activity index is significantly reduced, the porosity is significantly increased, and the electric flux increases accordingly. When there is no carbonization modification operation, the expansion value is increased, the activity index is reduced, the porosity reaches the highest, and the electric flux reaches the highest accordingly.
[0108] It can be seen that the composite auxiliary cementitious material modified from steel slag and carbide slag can significantly improve the various properties of the composite cementitious system. Changes in the liquid-solid ratio, carbonization enhancer, steel slag specific surface area, carbonization reaction conditions, additives and steel slag-carbide slag components will affect the carbonization efficiency of steel slag-carbide slag powder, and at the same time affect the various properties of the composite auxiliary cementitious material. In particular, the activity index of the composite auxiliary cementitious material ratio in Example 4 is the highest. As an auxiliary cementitious material, it exhibits high carbon fixation rate, high activity and good stability. It has low porosity and strong resistance to chloride ion penetration when used in cement concrete, indicating that it can be used as a green and low-carbon composite auxiliary cementitious material for cement concrete.
[0109] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag, characterized in that: The invention comprises the following raw materials in parts by weight: 40 to 55 parts of carbonated steel slag-carbide slag composite micropowder, 30 to 40 parts of high-titanium slag, 20 to 25 parts of metakaolin and 3 to 5 parts of phosphogypsum; the carbonated steel slag-carbide slag composite micropowder is obtained by carbon fixation reaction of steel slag and carbide slag in a solution consisting of a carbonization enhancer, an additive and water.
2. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 1, characterized in that: The method for preparing the carbonated steel slag-carbide slag composite micropowder comprises the following steps: 1) Grinding steel slag and a grinding aid in a ball mill to obtain steel slag powder; 2) mixing steel slag powder and carbide slag evenly to obtain steel slag-carbide slag composite powder; 3) The carbonization enhancer and water are mixed evenly, and then steel slag-carbide slag composite powder and additives are added in sequence. After mixing evenly, the mixture is placed in a carbonization reactor and CO2 is introduced to carry out carbon fixation reaction; 4) After the carbon fixation reaction is completed, solid-liquid separation is performed, ethanol is added to the solid material to terminate hydration, and the solid material is dried to obtain carbonated steel slag-carbide slag composite micropowder.
3. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 2, characterized in that: In the preparation method of the carbonated steel slag-carbide slag composite micropowder, the mass proportions of the raw materials used are: 20-35 parts of steel slag, 15-20 parts of carbide slag, 0.05-0.1 parts of grinding aid, 0.1-0.5 parts of carbonization enhancer, 0.05-0.1 parts of additives, and 280-550 parts of water.
4. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 2, characterized in that: The steel slag is converter steel slag, the grinding time is 1 to 1.5 hours, and the specific surface area of the steel slag powder is ≥450m 2 / kg; the grinding aid is composed of sodium tripolyphosphate and triisopropanolamine, and the mass ratio of sodium tripolyphosphate to triisopropanolamine is 1:(2.5-3); the carbide slag is carbide slag that is dried and stored in a vacuum dryer and sealed, and its moisture content is less than 1%, the Ca(OH)2 content is not less than 75%, and the specific surface area is 520-570m 2 / kg.
5. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 2, characterized in that: The carbonization enhancer is composed of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate, and the mass ratio of sodium tripolyphosphate, monosodium glutamate waste slurry and sodium citrate is (1.4-2):(3.8-4.4):1.5; the L-glutamic acid content of the monosodium glutamate waste slurry is 1.5-2%, the crude protein content is 70-80%, and the pH value is 3-4.
6. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 2, characterized in that: The additive is a mixture of polyvinyl alcohol and hydrogen peroxide, the concentration of the hydrogen peroxide is 1-1.2 mol / L, and the mass ratio of polyvinyl alcohol to hydrogen peroxide is (1.2-1.7):
1.
7. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 2, characterized in that: The reaction temperature of the carbon fixation reaction is 50-60°C, the reaction time is 60-90min, and the CO2 pressure is 0.3-0.5MPa.
8. The high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag according to claim 1, characterized in that: The high titanium slag has a TiO2 content of 10% to 15% and a specific surface area of 500 to 550 m 2 / kg, density is 2.6~2.9g / cm 3 The metakaolin is a highly active amorphous white powder obtained by calcining kaolin at 750-800°C, with a total content of SiO2 and Al2O3 ≥ 94.5%, a particle size ≤ 20 μm, a 2h ignition loss of 0.26-0.28, and a 28d activity index of 106-108%; the phosphogypsum is hemihydrate phosphogypsum, with a pH of 5.6-6.0 and a density of 2.2-2.4 g / cm 3 , with a specific surface area of 450-520m 2 / kg.
9. A method for preparing a high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The carbonated steel slag-carbide slag composite powder, high-titanium slag, metakaolin and phosphogypsum are uniformly mixed to obtain a high-activity composite auxiliary cementitious material.
10. An application of the high-activity composite auxiliary cementitious material based on carbonated steel slag-carbide slag as claimed in any one of claims 1 to 8, characterized in that: The application method is: the high-activity composite auxiliary cementitious material replaces part of the cement to prepare mortar or concrete; the mass replacement rate of the high-activity composite auxiliary cementitious material to cement is not higher than 50%.
Citation Information
Cited By
High-performance concrete of phosphogypsum-fly ash-slag multi-element solid waste system and preparation method of high-performance concrete
CN120365034A
Low-carbon cement clinker as well as preparation method and application thereof
CN120518334A
Low-carbon cement clinker, preparation method and application thereof
CN120518334B
Steel slag powder for solid waste-based cementing material and preparation method of steel slag powder
CN121085566A
Steel slag powder for solid waste-based cementitious materials and its preparation method
CN121085566B